MicroRNA-126: A new and promising player in lung cancer - Chen, Qijun (Oncol Lett, 2021)
Lung cancer is one of the most common malignant tumors associated with cancer death; however, the mechanisms involved in lung tumor development have not been completely elucidated, which impedes the advancement of clinical diagnosis and therapy. MicroRNA-126 (miR-126) is an important member of the microRNA family and is encoded by intron 7 of epidermal growth factor-like domain-containing gene 7. Increasing evidence has demonstrated that miR-126, as a distinct endothelial-enriched miRNA and new tumor suppressor gene, serves a promising role in the occurrence, development and metastasis of various types of cancer, including liver cancer, colorectal cancer, melanoma and lung cancer. In the present review, the current knowledge of the role of miR-126 in lung cancer growth, metastasis, diagnosis and prognosis as well as therapy was summarized, which may provide new insights on the biological roles of miRNAsin lung cancer and facilitate the ultimate development of miRNA-based therapies in clinical patients with non-small cell lung cancer.